Costly Mistakes: Why and When Spelling Errors in Resumes Jeopardise Interview Chances - Philippe Sterkens; Ralf Caers; Marijke De Couck; Michael Geamanu; Victor Van Driessche; Stijn Baert (Global Labor Organization (GLO), 2021)
Earlier research has associated spelling errors in resumes with reduced hiring chances. However, the analysis of hiring penalties due to spelling errors has thus far been restricted to white-collar occupations and relatively high numbers of errors per resume. Moreover, the mechanisms underlying the spelling error penalty have remained unclear. To fill these gaps in the peerreviewed literature, we conducted a scenario experiment with 445 genuine recruiters. Results show that, compared to error-free resumes, hiring penalties are being inflicted for both error-laden resumes (18.5 percent points lower interview probability) and resumes with fewer errors (7.3 percent points lower interview probability). Furthermore, we find substantial heterogeneity in penalties inflicted based on various applicant, job and participant characteristics. About half of the spelling error penalty can be explained by the perception that applicants who make spelling errors have lower interpersonal skills (9.0%), conscientiousness (12.1%) and mental abilities (32.2%).
Keywords: 330; spelling errors; resumes; signalling; hiring experiments